Preparation and properties of Ba1−xCaxTiO3 nanopowders obtained by mechanochemical synthesis. (2nd August 2016) - Szafraniak-Wiza, Izabela; Kozielski, Lucjan; Sebastian, Tutu
ABSTRACT: The calcium-substituted barium titanate nanopowders Ba1− x Ca x TiO3 (0.2 ≤ x ≤ 0.3) have been obtained at room temperature by mechanochemical synthesis. The formation of the perovskite phase was controlled by X-ray diffraction studies at various milling duration. The powders possess the perovskite crystallographic structure directly after milling longer than 10 h. The dielectric properties of the ceramics obtained by sintering of the nanopowders were investigated in the temperature range between 300 and 500 K. The temperature dependence of permittivity exhibited a single anomaly, which corresponds to the ferroelectric–paraelectric phase transition.